Telekom Malaysia Consumer Selangor (Kuala Lumpur) / Khairul Amira Khairuddin - Khairuddin, Khairul Amira (Perpustakaan Tengku Anis, 2018)
This industrial training report contains four (4) chapters. In chapter 1, it consist of the introduction with a sub topic of Background of the Organization and Organizational Structure. In chapter 2, the topic is Organization Structure with the sub topic of Departmental Structure and Function . Next topic for chapter 3 is Industrial Training Activities that can divide into three sub topic which are Training Activities, Special Project and Additional Activities. The last topic is Industrial Training Reflection Industrial Training five months of industrial training to complete these topic from the 1st February until 30 June 2018. The trainee undergone Industrial Training in TM Consumer Sales Selangor, Kuala Lumpur. Thus, during the industrial training period, the trainee is given a l f experience in work environment, gain more experience and knowledge.